The Role of Technology Start-ups in Driving Economic Growth Post-Pandemic - Khuan, Hendri; Rohim, Mohamad; Rukmana, Arief Yanto; Kurniawan, Ramdhan; Suprianus Pian TA (Westscience Press, 2023)
The COVID-19 pandemic triggered unprecedented disruptions across global economies, compelling various sectors to swiftly adapt to new realities. In this context, technology start-ups emerged as pivotal actors in driving post-pandemic economic growth. This study employs a comprehensive bibliometric analysis to elucidate the multifaceted role of technology start-ups in the recovery process. By systematically reviewing and analyzing a diverse corpus of scholarly literature, we uncover prevalent themes, influential authors, collaboration patterns, and keyword associations within this dynamic domain. Our findings reveal a surge in research output during the pandemic period, underscoring the urgency to understand the contributions of technology start-ups. Themes such as innovation, digital transformation, sustainable development, and global collaboration emerged prominently. Influential authors and institutions are identified, signaling thought leadership and collaborative networks. Moreover, the integration of Visualizing Output Similarities (VOS) Viewer analysis enhances our comprehension of thematic clusters and interrelationships. In conclusion, this bibliometric exploration provides insights that inform policy, industry, and academia, emphasizing the pivotal role of technology start-ups in shaping a resilient and innovative post-pandemic economic landscape.